Some metods of treatment bite patologies in children age - Olimov Siddiq Sharipovich; Safarova Mavludabony Jamolovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Annotation. In recent decades, tooth-jaw system anomalies and pathologies in different countries of the world have been increasing from year to year, and these pathologies, according to some authors(Khamadeeva and together avtori 2018, Persin and together avtori 2019), rank third after caries, parodontological diseases in terms of prevalence among dental diseases. According to the data cited by the World Health Organization, TJA was found among 50% of European children and adolescents, 83% of us 6-7-year-olds, 90% of Russia 6-7-year-olds, and among the remaining age contingents 41.8-61.28%, and during our study among 67.11% of 6-13-year-olds at the time of the examination, also the percentage of prevalence of TJA varies in different age groups. In particular, 70.8% occur among 6-9 age contingents, 79.3% between 10-13, and 68.5% between 14-16.(Gontarev, 2013, Yormukhamova 2021). As age grows in children and adolescents, several etiological causes, such as milk and permanent teeth disrupting the exit sequence, result in an increase in the amount of diseases cited above, increasing the demand for orthodontics and special orthodontic treatment. The following article provides a summary of some of the claimed methods of mesial Bite, a pathology of sagittal bite.